Decomposing productivity and efficiency changes in the Alaska head and gut factory trawl fleet. (December 2015) - Fissel, Benjamin E.; Felthoven, Ronald G.; Kasperski, Stephen; O'Donnell, Christopher
Abstract: Fishing fleets are subject to numerous factors that affect economic performance, making identification and attribution of such impacts difficult. This paper separately identifies the effects of changing input and output prices, fishery management, and quota allocations on total factor productivity using a Lowe Index. Indices account for technical change and decompose productivity estimates into its technical, environmental, and scale-mix components. This results in measures that reflect shifts in the production frontier, and movements by vessels toward and around the frontier, to capture economies of scale and mix after a policy shift to a catch share program that includes fishing cooperatives and a limited access fishery. The difference between cooperative and limited access vessels is exploited to compare the changes in economic performance between the groups after the introduction of the shift to catch shares and cooperative management, which allowed the vessels to improve the timing and coordination across multi-species fisheries and to decrease incidental catch of quota-limited bycatch species that had closed the target fisheries prematurely in the past. Results indicate that total factor productivity increased significantly after the move to a catch share program, largely due to increases in technical change that shifted out the production frontier of the fishery. Highlights: Total factor productivity is decomposed into technical, environmental, and scale-mix components. Productivity is estimated for the Alaska head and gut factory trawl fleet pre- and post-catch share implementation. Differences in timing of cooperative formation are exploited to compare the changes in economic performance between the groups. Total factor productivity increased with catch share program implementation, largely due to technical change that shifted out the production frontier.